IMPLEMENTASI MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS X TKRO 3 SMKN 2 YOGYAKARTA - Lukman Budhi Purnomo (Universitas Negeri Yogyakarta, 2019)
This study aims to determine whether the implementation of inquiry based learning is able to increase the student activity and learning outcomes of X TKRO 3 class at SMKN 2 Yogyakarta in Automotive Basic Engineering Subjects. This study is a Classroom Action Research using the Kemmis Mc Taggart design. Kemmis Mc Taggart's design includes the stages of planning, action observation, and reflection. The study subjects were X TKRO 3 class of SMKN 2 Yogyakarta 2018/2019 academic year totaling 32 students. Data collection techniques using the method of observation and test results. Data analysis used quantitative descriptive analysis. This is indicated by student learning activeness data of 60.71% in the first cycle and 62.67% in the second cycle. For student learning outcomes data, indicated by the class average value of 77,48 with the percentage of learning completeness of 85,2% in the first cycle and the class average of 91.56 with the percentage of learning completeness of 93,5% in the second cycle.